The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4066/amj.2014.2225
|View full text |Cite
|
Sign up to set email alerts
|

An unorthodox innervation of the gluteus maximus muscle and other associated variations: A case report

Abstract: Knowledge of peripheral nerve morphology, location, and variation is important for facilitating appropriate diagnosis and intervention. We present a unique case of absence of the inferior gluteal nerve and high division of the sciatic nerve. In this instance, the common peroneal nerve was found piercing the piriformis muscle and emerging distally in the form of two trunks: thin medial and thick lateral. The medial trunk presented an interesting course, supplying the gluteus maximus muscle before joining the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…One review showed that the IGN traverses superior to the PM in 0.1-4.4% of individuals [ 6 ]. The present case, like others, describes an instance where the nerve pierces the PM directly [ 7 , 8 ]; another case describes its complete absence [ 5 ]. Notably, these variants of the IGN appear to be strongly associated with ipsilateral splitting of the SN by the PM, possibly because these abnormalities have a shared embryological origin [ 5 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…One review showed that the IGN traverses superior to the PM in 0.1-4.4% of individuals [ 6 ]. The present case, like others, describes an instance where the nerve pierces the PM directly [ 7 , 8 ]; another case describes its complete absence [ 5 ]. Notably, these variants of the IGN appear to be strongly associated with ipsilateral splitting of the SN by the PM, possibly because these abnormalities have a shared embryological origin [ 5 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 86%
“…Sumalatha et al (2022) reported a case of an SN with a high division (i.e. the CFN and TN descended parallel to and independently of each other), and the IGN being absent [ 5 ]. They found that the CFN provided motor innervation to the GMax muscle in place of the missing IGN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation